2018
DOI: 10.1186/s12944-018-0763-z
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of low-density lipoprotein receptor (LDLR) mutations in a cohort of Sri Lankan patients with familial hypercholesterolemia – a preliminary report

Abstract: BackgroundHypercholesterolemia is a major determinant of cardiovascular disease-associated morbidity and mortality. Mutations in the LDL-receptor (LDLR) gene are implicated in the majority of the cases with familial hypercholesterolemia (FH). However, the spectrum of mutations in the LDLR gene in Sri Lankan patients has not been investigated. The objective of this study was to report the frequency and spectrum of variants in LDLR in a cohort of Sri Lankan patients with FH.MethodsA series of consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…One patient was compound heterozygous for LDLR c.2289 G > T (p.E763D) and LDLR c.1670 C > G (p.T557S). The study found that LDLR mutations were markedly low in this population ( Paththinige et al, 2018 ).…”
Section: Genetic Diagnosis Of Fh In Asiamentioning
confidence: 71%
“…One patient was compound heterozygous for LDLR c.2289 G > T (p.E763D) and LDLR c.1670 C > G (p.T557S). The study found that LDLR mutations were markedly low in this population ( Paththinige et al, 2018 ).…”
Section: Genetic Diagnosis Of Fh In Asiamentioning
confidence: 71%
“…The expressions of CYP7A1and LDLR in the EMZAP-treated groups (the Low Group and the High Group) was increased compared with the Model Group. The increased expressions of these two genes were capable of reducing the cholesterol content in the plasma [26,27]. The increased expression of LXRα has been shown to improve hyperlipidemia and prevent atherosclerosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlipidemia is a common genetic disorder inherit by genetic mutations mostly in LDLR, apoB-100, or proprotein convertase subtilisin kexin type 9 (PCSK9) loci which can result in xanthoma, atherosclerosis, coronary atherosclerotic heart disease (CAD), and other cardiovascular diseases [ 12 ]. The majority (60–80%) of the patients with family hyperlipidemia (FH) harbor mutations in the LDLR gene [ 13 ], but apoE serves as a major member of many ligands of LDLR which can transport plasma chylomicrons and VLDL cholesterol to the liver for metabolism by LDL receptor and related receptors. As a result, LDLR and apoE, especially the LDLR, play a critical role for the clearance of lipoprotein remnant.…”
Section: Discussionmentioning
confidence: 99%